Spatial-temporal evolution and prediction of habitat quality in the Yellow River Basin - Hou, Yanjun; Wu, Juemei; Guo, Yanxi (Frontiers in Environmental Science, 2025)
Assessment and predictive analysis of the ecological environment quality of river basins are important for achieving coordinated development between ecological protection and high-quality development. In this study, we simulated and analyzed the spatiotemporal patterns of future land use and habitat quality in the Yellow River Basin using the PLUS and InVEST models. The results show that: (1) from 2000 to 2020, grassland, cultivated land, and forest land dominated the land categories, with a continuous loss of cultivated land and rapid expansion of construction land; (2) under the natural development scenario (NG-S), construction land expanded significantly; under the ecological protection scenario (EP-S), grassland increased; under the cultivated land protection scenario (AP-S), cultivated and construction land increased while ecological land decreased; and under the coordinated development scenario (CEPAP-S), cultivated land and grassland increased slightly; (3) overall stability was observed from 2000 to 2020, but with an internal trend of “polarization”; and (4) in the future, only the EP-S and CEPAP-S scenarios are projected to improve habitat quality, whereas other scenarios would lead to degradation.